A Clinical Examination of Patients with Chronic Rhinitis Using Paranasal Sinus Radiography Technique: A Case Study - Zunicha Putri, Selly (Infomasi dan Promosi Kesehatan, 2023)
Chronic rhinitis is a disease that causes hypertrophy of the nasal concha which can lead to sinusitis, especially in the maxilla sinus and ethmoid sinus. Early detection of chronic rhinitis can use paranasal sinus radiographic techniques with parietoacanthial (PA) waters closed mouth and postero-anterior (PA) caldwell projections. The purpose of the study was to determine the reasons and role of using PA waters closed mouth and PA caldwell projections in paranasal sinus radiographic techniques in the early detection of chronic rhinitis cases. In this study, data analysis was obtained from observation data, interviews, documentation, literature studies, and questionnaires processed using SPSS 23 calculations. This study shows the technique of paranasal sinus radiography in cases of chronic rhinitis there is no special preparation, the patient only removes metal objects around the object being examined. Tools and materials imaging plate size 18 x 24 cm with collimation area adjusted to the object, conventional aircraft CR, bucky stand, marker and processing tools. The reason for using projections from the validity test results using SPSS 23 is seen from the effects of chronic rhinitis which can cause sinusitis, especially the maxilla sinus and ethmoid sinus, the PA waters closed mouth projection of the maxilla sinus anatomy looks very good and PA caldwell projection of the ethmoid sinus anatomy looks good. The role of both projections is able to show the thickening of the nasal concha, fluid boundaries in the maxilla sinus, septum nasi, cavum nasi, ethmoid sinus, frontal sinus, and maxilla sinus.